Functional characterization of CDK10 and cyclin M truncated variants causing severe developmental disorders. Issue 10 (9th August 2021) - Robert, Thomas; Dock‐Bregeon, Anne‐Catherine; Colas, Pierre
Abstract: Background: CDK10 is a poorly known cyclin M (CycM)‐dependent kinase. Loss‐of‐function mutations in the genes encoding CycM or CDK10 cause, respectively, STAR or Al Kaissi syndromes, which present a constellation of malformations and dysfunctions. Most reported mutations abolish gene expression, but two mutations found in 3' exons could allow the expression of CDK10 and CycM truncated variants. Methods: We built a structural model that predicted a preserved ability of both variants to form a CDK10/CycM heterodimer. Hence, we functionally characterized these two truncated variants by determining their capacity to heterodimerize and form an active protein kinase when expressed in insect cells, by examining their two‐hybrid interaction profiles when expressed in yeast, and by observing their expression level and stability when expressed in human cells. Results: Both truncated variants retain their ability to form a CDK10/CycM heterodimer. While the CycM variant partially activates CDK10 activity in vitro, the CDK10 variant remains surprisingly inactive. Expression in human cells revealed that the CDK10 and CycM variants are strongly and partially degraded by the proteasome, respectively. Conclusion: Our results point to a total loss of CDK10/CycM activity in the Al Kaissi patient and a partial loss in the STAR patients. Abstract : Loss‐of‐function mutations in the genes encoding CycM or CDK10 cause, respectively, STAR or Al Kaissi syndromes, which present a constellation of malformations and dysfunctions. We have functionally characterized truncated CDK10 and CycM variants, focusing on their ability to heterodimerize and form an active kinase. Our results point to a total and partial loss of CDK10/CycM activity in the Al Kaissi and the STAR patients, respectively.